Evading Responsibility: A Structural Critique of Living Wage Initiatives and Methodologies - Justine Coneybeer; Rowena Maguire (International Journal for Crime, Justice and Social Democracy, 2022)
Despite the existence of multiple living wage initiatives and methodologies for calculating a living wage, there has been limited improvement in increasing garment workers’ incomes. This paper applies Iris Marion Young’s responsibility for structural injustice theory to connect apparel brands and retailers as the actors with power, privilege and capacity to enact change to improve poverty wages. This paper critically analyses two living wage methodologies and three living wage initiatives, drawing upon Young’s theory to understand why progress on living wage has stagnated. The analysis also considers whether gender has been incorporated, finding that most methodologies and initiatives fail to adequately embed gendered considerations. Findings reveal that the most powerful actors in apparel global values chains (brands and retailers) evade responsibility through performative membership with initiatives that prioritise profit, ignore gendered considerations and require minimum changes from businesses as usual.